MAIT cell activation is reduced by direct and microbiota-mediated exposure to bisphenols. (January 2022) - Krause, J.L.; Engelmann, B.; Nunes da Rocha, U.; Pierzchalski, A.; Chang, H.D.; Zenclussen, A.C.; von Bergen, M.; Rolle-Kampczyk, U.; Herberth, G.
Graphical abstract: Abstract: Oral uptake is the primary route of human bisphenol exposure, resulting in an exposure of the intestinal microbiota and intestine-associated immune cells. Therefore, we compared the impact of bisphenol A (BPA), bisphenol F (BPF) and bisphenol S (BPS) on (i) intestinal microbiota, (ii) microbiota-mediated immunomodulatory effects and (iii) direct effects on mucosal-associated invariant T (MAIT) cells in vitro . We acutely exposed human fecal microbiota, Bacteroides thetaiotaomicron and Escherichia coli to BPA and its analogues BPF and BPS referring to the European tolerable daily intake (TDI), i.e. 2.3 µg/mL, 28.3 µg/mL and 354.0 µg/mL. Growth and viability of E. coli was most susceptible to BPF, whereas B. thetaiotaomicron and fecal microbiota were affected by BPA > BPF > BPS. At 354.0 µg/mL bisphenols altered microbial diversity in compound-specific manner and modulated microbial metabolism, with BPA already acting on metabolism at 28.3 µg/mL. Microbiota-mediated effects on MAIT cells were observed for the individual bacteria at 354.0 µg/mL only. However, BPA and BPF directly modulated MAIT cell responses at low concentrations, whereby bisphenols at concentrations equivalent for the current TDI had no modulatory effects for microbiota or for MAIT cells. Our findings indicate that acute bisphenol exposure may alter microbial metabolism and impact directly on immune cells.